THE SOCIAL SIGNIFICANCE OF THE INTERCULTURAL APPROACH IN TEACHING PROFESSIONAL ENGLISH COMMUNICATION TO STUDENTS OF THE LOGISTICS FIELD - Botirova Palina Khakimjonovna (Journal Park Publishing, 2025)
In the context of global economic integration, logistics is one of the most dynamically developing fields that requires specialists capable of interacting effectively in a multicultural and multilingual environment. The teaching of professional English communication in logistics education, therefore, cannot be reduced merely to the acquisition of linguistic competence. It must be oriented towards the formation of intercultural communicative competence, which ensures mutual understanding, tolerance, and successful cooperation among representatives of different cultural systems. This article explores the social significance of the intercultural approach in teaching professional English to logistics students, emphasizing its pedagogical, cultural, and socio-economic dimensions. The work integrates the ideas of Uzbek and foreign scholars such as D. M. Isroilova, U. S. Begimkulov, M. Byram, and C. Kramsch, and analyzes how intercultural-oriented language education contributes to social cohesion, global citizenship, and professional efficiency in the logistics sector.
Keywords: Intercultural approach, logistics education, English for Specific Purposes (ESP), professional communication, social competence, globalization.